Manajemen Logistik Obat di Instalasi Farmasi RSUD Kota Dumai Tahun 2021 - Ovi Novianto Siska; Doni Jepisah (Universitas Batanghari Jambi, 2022)
Pharmacy Installation is a functional implementing unit that organizes all pharmaceutical service activities in hospitals. Based on the preliminary survey, it was found that the planning of drug needs at the Dumai City Hospital, the use of drugs has not been in accordance with the actual needs, there are still many types of drugs that have an excess amount of remaining stock and insufficient drugs, there are still drugs that have the same efficacy in large quantities in Indonesia. In planning, there are still several types of drugs that are requested in the amount that is not in accordance with what is received. Residency method is qualitative using USG and Fishbone method. There are 2 informants in the residency with the subject of 1 Head of Pharmacy Installation and 1 Pharmacy staff. The results of the identification of the problem found that there were still the types of drugs that were requested, the quantities did not match what was received, there were still many types of drugs that had excess stock and insufficient drugs, there was no reward and punishment was not optimal and there was no vision and mission of the pharmacy installation. . The priority of the problem is that there are still types of drugs that are requested, the amount does not match those received by the pharmacy installation, a total score of 12. Recommendations for conducting a re-assessment of more and less drugs, re-assessing the rewards for officers who excel, especially officers who excel in the installation pharmacy, making its own vision and mission in the pharmacy installation so that the goals are more focused, there needs to be deeper communication from the hospital management and the drug providers.